How do health workers experience and cope with shocks? Learning from four fragile and conflict-affected health systems in Uganda, Sierra Leone, Zimbabwe and Cambodia - Witter, Sophie; Wurie, Haja; Chandiwana, Pamela; Namakula, Justine; Alonso-Garbayo, Alvaro; Ssengooba, Freddie; Raven, Joanna; So, Sovannarith (Health Policy and Planning, 2017)
This article is grounded in a research programme which set out to understand how to rebuild health systems post-conflict. Four countries were studied—Uganda, Sierra Leone, Zimbabwe and Cambodia—which were at different distances from conflict and crisis, as well as having unique conflict stories. During the research process, the Ebola epidemic broke out in West Africa. Zimbabwe has continued to face a profound economic crisis. Within our research on health worker incentives, we captured insights from 128 life histories and in-depth interviews with a variety of staff that had remained in service. This article aims to draw together lessons from these contexts which can provide lessons for enhancing staff and therefore health system resilience in future, especially in similarly fragile and conflict-affected contexts. We examine the reported effects, both personal and professional, of the three different types of shock (conflicts, epidemics and prolonged political-economic crises), and how staff coped. We find that the impact of shocks and coping strategies are similar between conflict/post-conflict and epidemic contexts—particularly in relation to physical threats and psychosocial threats—while all three contexts create challenges and staff responses for working conditions and remuneration. Health staff showed considerable inventiveness and resilience, and also benefited from external assistance of various kinds, but there are important gaps which point to ways in which they should be better protected and supported in the future. Health systems are increasingly fragile and conflict-prone, and shocks are often prolonged or repeated. Resilience should not be taken for granted or used as an excuse for abandoning frontline health staff. Strategies should be in place at local, national and international levels to prepare for predictable crises of various sorts, rather than waiting for them to occur and responding belatedly, or relying on personal sacrifices by staff to keep services functioning.
Keywords: Health workers; resilience; conflict; economic shocks; Ebola; coping strategies; Sierra Leone; Zimbabwe; Uganda